2022
DOI: 10.1111/jfpe.14076
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time equilibrium moisture content monitoring to predict grain quality of corn stored in silo and raffia bags

Abstract: The use of silo and raffia bags for the temporary grain storage has been increasing in recent years. However, the methods for monitoring a stored product are limited to visual inspections and sampling. Thus, this research aimed to real-time equilibrium moisture content monitoring to predict grain quality of corn stored in different conditions in silo and raffia bags using wireless sensor network prototype, Internet of Things (IoT) platform, and neural network algorithms. Experiments were conducted using corn g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…After calibration of the sensors at time zero, there was a reduction in temperature and an increase in relative humidity and intergranular CO 2 , with a tendency for the curves to stabilize over time. These findings demonstrate the consistency of the monitored variables, as well as the accuracy and functionality of the monitoring system 28 .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…After calibration of the sensors at time zero, there was a reduction in temperature and an increase in relative humidity and intergranular CO 2 , with a tendency for the curves to stabilize over time. These findings demonstrate the consistency of the monitored variables, as well as the accuracy and functionality of the monitoring system 28 .…”
Section: Resultssupporting
confidence: 58%
“…After calibration of the sensors at time zero, there was a reduction in temperature and an increase in relative humidity and intergranular CO 2 , with a tendency for the curves to stabilize over time. These findings demonstrate the consistency of the monitored variables, as well as the accuracy and functionality of the monitoring system 28 .
Figure 3 Temperature and relative humidity of corn grain mass with 12% ( A ), 16% ( B ), 25% ( C ) moisture contents in tube with holes of 6.5, 7.0 and 7.5 mm and drilling heights of 117.5, 235 and 470 mm.
…”
Section: Resultssupporting
confidence: 58%
“…It was shown that temperature and water activity are important environmental factors affecting the growth of pathogenic fungi and mycotoxin production in paddy [ 9 ]. Lutz et al [ 10 ] used techniques such as wireless sensor network prototypes and neural network algorithms to predict the grain quality of corn stored in silos and raffia bags under different conditions, and experiments showed that storage time had an effect on grain quality decline for all factors. Therefore, it is crucial to maintain a proper storage environment to preserve the quality of paddy grains during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Faree et al [2] used multiple linear regression and the artificial neural network (ANN) to predict the quality of maize grains during storage; they achieved better prediction results. Lutz et al [5] used a wireless sensor network, an IoT platform, to monitor the equilibrium moisture content in real time and used ANN to predict the quality of maize grains stored under different conditions. Szwedziak et al [6] used a proprietary computer application based on the RGB model to assess the contamination status of maize grains.…”
Section: Introductionmentioning
confidence: 99%